2012
DOI: 10.5120/7620-0674
|View full text |Cite
|
Sign up to set email alerts
|

Stemming Effectiveness in Clustering of Arabic Documents

Abstract: Clustering is an important task gives good results with information retrieval (IR), it aims to automatically put similar documents in one cluster. Stemming is an important technique, used as feature selection to reduce many redundant features have the same root in root-based stemming and have the same syntacticalform in light stemming. Stemming has many advantages it reducesthe size of document and increases processing speed and used in many applications as information retrieval (IR). In this paper, we have ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In a study presented in Ghanem and Ashour [44], the effect of using full-word, stem, and root forms on clustering of Arabic documents was discussed. The comparison was based on different measures of precision, recall, and F-measure.…”
Section: Related Workmentioning
confidence: 99%
“…In a study presented in Ghanem and Ashour [44], the effect of using full-word, stem, and root forms on clustering of Arabic documents was discussed. The comparison was based on different measures of precision, recall, and F-measure.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of the Arabic language, stemming has been the subject of several studies that have shown its effectiveness in both text classification and clustering [4], [6], [19], [20]. However, three recent comparative studies investigated different Arabic stemmers in the field of Arabic text classification.…”
Section: Stemmingmentioning
confidence: 99%
“…Ghanem and Ashour [13] established that clustering plays a fundamental role in achieving good results during IR. The use of stemming techniques enables the reduction of redundant features that have similar roots in root‐based stemming and ones that exhibit the same syntactical form.…”
Section: Literature Reviewmentioning
confidence: 99%